Enhanced recovery after surgery (ERAS) in gynecology oncology. Issue 5 (May 2021) - Bogani, Giorgio; Sarpietro, Giuseppe; Ferrandina, Gabriella; Gallotta, Valerio; DI Donato, Violante; Ditto, Antonino; Pinelli, Ciro; Casarin, Jvan; Ghezzi, Fabio; Scambia, Giovanni; Raspagliesi, Francesco
Abstract: The Enhanced Recovery After Surgery (ERAS) is a pathway designed to achieve early recovery for patients undergoing major surgery. The ERAS pathway included three important components preoperative, intraoperative, postoperative program. Pre-habilitation and re-habilitation are of paramount importance to improve patients' care. The ERAS is based on evidence-based medicine. Accumulating evidence highlighted that adopting ERAS resulted in lower complication rate, and shorter length of hospital stay in comparison to standard protocols of care. The adoption of the ERAS resulted in a significant improvement of patients' outcomes and a reduction of the overall cost of care. In the present review, we summarized current evidence on ERAS, focusing on the steps useful for its adoption into clinical practice .